2018
DOI: 10.1002/rcm.8171
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of nitrogen and carbon isotopes from fish diets to otoliths as measured by nanoscale secondary ion mass spectrometry

Abstract: These results suggest that otolith nitrogen and carbon isotopes from food were directly assimilated on the same day. Food is the major and in some cases only source of otolith nitrogen isotopes but makes only a partial contribution to otolith carbon isotopes. Therefore, the δ N values recorded in the sclerochronological layers of the otoliths can be used to determine the trophic levels, food sources and diet changes of fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…A recent study using the addition method suggested that otolith nitrogen isotopes were directly assimilated from food on the day that it was fed to the fish . The results of this study further suggest that the otolith organic matrix was derived from the food ingested by fish, with little, if any, nitrogen isotope fractionation.…”
Section: Discussionsupporting
confidence: 62%
“…A recent study using the addition method suggested that otolith nitrogen isotopes were directly assimilated from food on the day that it was fed to the fish . The results of this study further suggest that the otolith organic matrix was derived from the food ingested by fish, with little, if any, nitrogen isotope fractionation.…”
Section: Discussionsupporting
confidence: 62%
“…We recommend further future work that should include a compilation of published research on movements of predators and their diets from stomach contents and other techniques, to provide greater insights into the role predation plays in the accumulation of otoliths into sediments. For example, to investigate the degree to which trophic physiological relationships changed from the mid-Holocene to today using carbon and nitrogen isotopes from otoliths [9799].…”
Section: Discussionmentioning
confidence: 99%
“…Controlled laboratory experiments demonstrate stable isotopes of otolith organics are effective tracers of diet (e.g., Grønkjaer et al 2013;Lueders-Dumont et al 2020, with dietary tracing ability of otoliths immune to temperature effects (Godiksen et al 2019). Overall, otolith proteins rapidly incorporate N from diet (Shiao et al 2018) and in timescales similar to liver, the tissue with the shortest turnover time (Lueders-Dumont et al 2022). However, life history stage must be considered, especially for young fish, which may have smaller trophic discrimination factors, including for otoliths (Lueders-Dumont et al 2022).…”
Section: Groundtruthing Stable Isotope Composition Of Otolith Protein...mentioning
confidence: 99%